The Welfare of Cattle in Different Housing Systems - Bogumiła Pilarczyk; Renata Pilarczyk; Małgorzata Bąkowska; Agnieszka Tomza-Marciniak; Beata Seremak; Ewa Kwita; Marta Juszczak-Czasnojć; Paulius Matusevičius; Ramutė Mišeikienė (Animals, 2025)
The review provides an overview of research concerning the assessment of cattle welfare in different housing systems. Hence, it restricts its scope to factors known to have a particular influence on the expression of their natural behaviours. It analyses the impact of housing systems on social and maternal bonds, as well as on the health and productivity of animals and on the feeding behaviour and physical activity of animals. It also pays attention to the occurrence of stereotypies, indicating the quality of the environment in which animals live, and attempts to determine the extent to which environmental enrichment improves welfare. It can be seen that welfare can vary significantly depending on the cattle rearing system. In intensive rearing environments, weaning calves and limited space often result in stress and behavioural disorders (e.g., cross-sucking). Extensive systems, offering access to pasture and longer cow–calf contact, usually provide higher levels of welfare. A freestall system allows greater freedom of movement and social contact but requires appropriate management to prevent aggression; in contrast, the tethering system limits movement, which increases the risk of stress and health problems. It has also been shown that enriching the living space of animals can significantly improve their welfare, regardless of the housing system. By balancing productivity with ensuring that the cattle are able to express their natural behaviours and maintain good health, it is possible to benefit both the animals and the agricultural sector as a whole, increasing its profitability and gaining consumer confidence.